Climate Change and Florida: Frequently Asked Questions - Joshua Papacek; Ashley Smyth; Holly Abeels; Alicia Betancourt (EDIS)
Climate change is considered one of the biggest challenges facing society. As global temperatures continue to rise, we are threatened by melting ice sheets, rising sea levels, and extreme weather events. Climate change is also something that the people in south Florida live with daily. Still, the science of climate change is complicated, leaving many in the region looking for trusted information about why climate should matter to them. The purpose of this new 8-page FAQ document is to provide answers to commonly asked questions regarding climate change. The questions come from south Florida residents and municipal workers concerned with the climate outcomes to their region. The FAQ address several areas of concerns, including the basic science behind climate change, the projected impacts to residents of south Florida, and actions that individuals can take to reduce their carbon footprints. Written by Joshua Papacek, Ashley Smyth, Holly Abeels, and Alicia Betancourt, and published by the UF/IFAS Department of Soil and Water Sciences. https://edis.ifas.ufl.edu/ss682